Effects of enrichment media and incubation conditions on isolating salmonellae from ground-meat filtrate. - Kafel, S (1977)
Forty-eight combinations of enrichment media, secondary enrichment, incubation times and temperatures, and atmospheres were examined for their efficacy in recovering different serovars of Salmonella that had been inoculated into ground-meat extract. Variations included three selective-enrichment media, two (37 and 43 degrees C) incubation temperatures, two (24 and 48 h) incubation times, two (aerobic and anaerobic) incubation atmospheres, and secondary enrichment to two of the selective-enrichment media. The ratio of Salmonella to other microorganisms was 10: greater than 1,000,000. One-hundred and twenty-four tests were conducted for each enrichment under each condition of incubation. None of the methods recovered Salmonella in more than 60% of the trials. Salmonella typhimurium was recovered most frequently of the serovars tested; S. abortusovis was recovered least frequently. There was considerable variation in the results obtained by the different methods, but there was a statistically significant advantage in the 43 degrees C incubation temperature. Secondary enrichment in tetrathionate broth showed a statistically significant advantage over secondary enrichment in selenite broth. Secondary enrichment into a different medium from the primary enrichment also was advantageous.